2022
DOI: 10.1007/s10198-022-01514-1
|View full text |Cite
|
Sign up to set email alerts
|

The long-term cost-effectiveness of once-weekly semaglutide 1 mg vs. dulaglutide 3 mg and 4.5 mg in the UK

Abstract: Aims Once-weekly semaglutide and dulaglutide represent two highly efficacious treatment options for type 2 diabetes. A recent indirect treatment comparison (ITC) has associated semaglutide 1 mg with similar and greater improvements in glycated haemoglobin (HbA1c) and body weight, respectively, vs. dulaglutide 3 mg and 4.5 mg. The present study aimed to evaluate the long-term cost-effectiveness of semaglutide 1 mg vs. dulaglutide 3 mg and 4.5 mg in the UK. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The results of extracted data from included studies can be found in Table 1, which summarises the general characteristics of the studies. The majority of studies (n = 30) were conducted in Europe , of which many were conducted in the UK (n = 9) [37,38,40,45,46,48,51,57,62], and one-third of the studies were conducted in North America (n = 10) [64][65][66][67][68][69][70][71][72][73] and Asia (n = 8) [74][75][76][77][78][79][80][81]. Two studies were conducted outside these regions: one each from Colombia [82] and Iran [83].…”
Section: Basic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of extracted data from included studies can be found in Table 1, which summarises the general characteristics of the studies. The majority of studies (n = 30) were conducted in Europe , of which many were conducted in the UK (n = 9) [37,38,40,45,46,48,51,57,62], and one-third of the studies were conducted in North America (n = 10) [64][65][66][67][68][69][70][71][72][73] and Asia (n = 8) [74][75][76][77][78][79][80][81]. Two studies were conducted outside these regions: one each from Colombia [82] and Iran [83].…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…Explicit reasoning for the choice of risk equation was only present in a few cases. Three studies with SGLT2 as the main comparator cited model fit as the reason [40,45,56], while eight GLP1 studies cited advice from model proprietors as the reason [37,38,47,49,57,[61][62][63]. Different aspects of the risk equations were sometimes used simultaneously.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…23 Similar analyses have evaluated the long-term cost-effectiveness of oral semaglutide versus empagliflozin and dulaglutide in Portugal, and one time per week injectable semaglutide versus high-dose dulaglutide and liraglutide in the UK. [24][25][26] However, questions remain over the impact of introducing oral semaglutide versus continuing therapy with the oral agents recommended by NICE, specifically metformin plus an SGLT-2 inhibitor, and the present study aimed to build on these previous analyses to address this pertinent research question using similar methodology.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%